Assessing the eco-effectiveness of energy R&D technologies and environmental patents: A comparison between Portugal and Spain - Ugur Korkut Pata (Sustainable Futures)
The validity of environmental hypotheses is important for the implications of a sustainable future. In this context, this study investigates the validity of the Environmental Kuznets Curve (EKC) and the load capacity curve (LCC) for Portugal and Spain. Employing the Fourier-ADL approach from 1983 to 2020, the study concludes that the EKC and LCC hypotheses are valid for both countries, that environmental patents improve ecological quality, but that energy-related R&D expenditures have no significant impact. The findings underline the need to support environmental patents with income growth to ensure a sustainable future.